Convergent evolution of the arginine deiminase pathway: the ArcD and ArcE arginine/ornithine exchangers - Noens, Elke E. E. (Microbiologyopen, 2016)
The arginine deiminase (ADI) pathway converts L‐arginine into L‐ornithine and yields 1 mol of ATP per mol of L‐arginine consumed. The L‐arginine/L‐ornithine exchanger in the pathway takes up L‐arginine and excretes L‐ornithine from the cytoplasm. Analysis of the genomes of 1281 bacterial species revealed the presence of 124 arc gene clusters encoding the pathway. About half of the clusters contained the gene encoding the well‐studied L‐arginine/L‐ornithine exchanger ArcD, while the other half contained a gene, termed here arcE, encoding a membrane protein that is not a homolog of ArcD. The arcE gene product of Streptococcus pneumoniae was shown to take up L‐arginine and L‐ornithine with affinities of 0.6 and 1 μmol/L, respectively, and to catalyze metabolic energy‐independent, electroneutral exchange. ArcE of S. pneumoniae could replace ArcD in the ADI pathway of Lactococcus lactis and provided the cells with a growth advantage. In contrast to ArcD, ArcE catalyzed translocation of the pathway intermediate L‐citrulline with high efficiency. A short version of the ADI pathway is proposed for L‐citrulline catabolism and the presence of the evolutionary unrelated arcD and arcE genes in different organisms is discussed in the context of the evolution of the ADI pathway.